HUBUNGAN KELOMPOK TEMAN SEBAYA (PEER GROUP) DENGAN PRESTASI BELAJAR SISWA KELAS XII IPS DI SMAN 1 PADANG GANTING KECAMATAN PADANG GANTING KABUPATEN TANAH DATAR - Martalena, Martalena; Pramono, Wahyu; Melia, Yenni (Pendidikan Sosiologi, 2013)
Based on background of the problem of this research that teenagers interaction influence each other and act base on their peer group. So, the bad relationship of peer group in society and school environment can influence behaviour of teenager and act in their social environment the formulation of the problem that related in this research, wheather there is peer group relationship with students achievement in SMAN 1 Padang Ganting. The purpose of the study to analyze peer group relationship with students achievement in SMAN 1 Padang Ganting.This research located in SMAN 1 Padang Ganting the population and sample of research is 59 students in class XII IPS SMAN 1 Padang Ganting, but because there was same students score annoyed data entry,so sample becomes 48 students and technique of gathering data by used and questionnaire directly to the object, students of SMAN 1 Padang Ganting. This research is ex-post facto with correlation type that have purpose to know there is relationship beetwen two variables or not.From the analyze of data about peer relationship (peer group), students achievement in class XII IPS that consist of 48 student, we known rhitung 0,145 < rtabel 0,264. Its means of relationship with X variable and Y variable was low. Later, to test that relationship significant of variable X with variable Y which t test. Based on the result of calculation we known thitung = 1,015, while ttabel = 1,684. This showed value of thitung less than ttabel, or with another word relationship between X variable and Y variable was not significant. The result of this research that concluded there is no significant relationship between peer group with student achievemen.